Prostate Cancer Imaging. Computer-Aided Diagnosis, Prognosis, and Intervention International Workshop, Held in Conjunction with MICCAI 2010, Beijing,China, September 24, 2010. Proceedings - Madabhushi, Anant; Dowling, Jason; Yan, Pingkun; Fenster, Aaron; Abolmaesumi, Purang; Hata, Nobuhiko; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the International Workshop on Prostate Cancer Imaging, held in conjunction with MICCAI 2010, in Beijing, China, in September 2010. The 11 revised full papers presented together with 2 invited talks were carefully reviewed and selected from 13 submissions. The papers cover the clinical areas radiology, radiation oncology, digital pathology, and image guided intervention, addressing topics such as prostate segmentation, multi-modal prostate registration, computer-aided diagnosis and classification of prostate cancer.
Prostate Cancer MR Imaging -- Computer Aided Detection of Prostate Cancer Using T2, DWI and DCE MRI: Methods and Clinical Applications -- Prostate Cancer Segmentation Using Multispectral Random Walks -- Automatic MRI Atlas-Based External Beam Radiation Therapy Treatment Planning for Prostate Cancer -- An Efficient Inverse-Consistent Diffeomorphic Image Registration Method for Prostate Adaptive Radiotherapy -- Atlas Based Segmentation and Mapping of Organs at Risk from Planning CT for the Development of Voxel-Wise Predictive Models of Toxicity in Prostate Radiotherapy -- Realtime TRUS/MRI Fusion Targeted-Biopsy for Prostate Cancer: A Clinical Demonstration of Increased Positive Biopsy Rates -- HistoCAD: Machine Facilitated Quantitative Histoimaging with Computer Assisted Diagnosis -- Registration of In Vivo Prostate Magnetic Resonance Images to Digital Histopathology Images -- High-Throughput Prostate Cancer Gland Detection, Segmentation, and Classification from Digitized Needle Core Biopsies -- Automated Analysis of PIN-4 Stained Prostate Needle Biopsies -- Augmented Reality Image Guidance in Minimally Invasive Prostatectomy -- Texture Guided Active Appearance Model Propagation for Prostate Segmentation -- Novel Stochastic Framework for Accurate Segmentation of Prostate in Dynamic Contrast Enhanced MRI -- Boundary Delineation in Prostate Imaging Using Active Contour Segmentation Method with Interactively Defined Object Regions.
Keywords: Computer science; Computer simulation; Computer vision; Computer graphics; Optical pattern recognition; Computer Science; Image Processing and Computer Vision; Pattern Recognition; User Interfaces and Human Computer Interaction; Computer Graphics; Computer Imaging, Vision, Pattern Recognition and Graphics; Simulation and Modeling